ANALISIS TEORI BELAJAR KOGNITIF DAN IMPLIKASINYA DALAM PEMBELAJARAN MATEMATIKA DI SD - Sugiarti, Nani; Nirmala, Sri Dewi (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This research aims to analyze the cognitive learning theories proposed by Jean Piaget, Jerome Bruner, Robert Gagné, and David Ausubel, as well as their implications in elementary school mathematics education. The subjects of this research are 4th-grade elementary school students at SDIT AL-IMAN Bojongsari Depok, Indonesia. The research instruments used include literature documentation, interviews, questionnaires, and observations. The research data were analyzed using thematic analysis methods to identify patterns and main themes that emerged from the qualitative data. Data triangulation was conducted by combining results from various research instruments to validate the findings. The results of the analysis show that the application of these cognitive theories can enhance students' understanding of mathematical concepts, problem-solving skills, and learning motivation. Cognitive learning theories in elementary school mathematics education have significant implications for both teachers and students. By applying these theories, mathematics education in elementary schools can become more meaningful, effective, and enjoyable for students. This will help students develop their thinking skills and prepare them to face future challenges